Managing waste product of avocado (skin & stone) as ink/dye / Nur Muhammad Ameriqhwan Ahmad Faiza, Siti Nurfahana Ezety Mohamad and Siti Zulaikha Che Ismail - Ahmad Faiza, Nur Muhammad Ameriqhwan; Mohamad, Siti Nurfahana Ezety; Che Ismail, Siti Zulaikha (Faculty of Plantation and Agrotechnology, 2023)
Since there is an increase in avocado consumption worldwide, whether it be fresh or in the form of processed goods, several nations have made significant investments in avocado cultivation. Avocado industrial- isation produces a significant quantity of trash, including the peel and stone. These biomasses might be transformed into raw materials to produce various co-products. We need to maximise the amount of the agricultural waste coming from the avocado industry. By saying that, the avocado stone and peel can be turned into natural ink/dye that have no chemical inside it. The methods that being used are easy without needing any special tools. The avocado peel will be boiled with water on the stove for about an hour to bring out the colour from it. We can find that the colour that comes from the avocado peels are dark pink. This colour can be use as ink or dye that is non-toxic to the environment. Nowadays, a lot of people will prefer sustainable product over any synthetic because this can be refer in kind’s garment due to its anti- allergy and non-toxicities properties (Gopala krishnan et al., 2021). We can conclude that it is feasible to create more environmentally friendly goods that add value to the waste created during the processing of avocados by utilising components with high biological value. This natural dye has a potential to utilize avocado waste and reduce environmental pollution.